Analysis of Work Motivation and Employee Performance in Micro Coffee Businesses in Medan City, Medan Petisah District in 2021 - Dorene Syahfitri (Journal Arbitrase : Economy, Management and Accounting, 2025)
Employee work motivation and performance are very important factors. in maintaining company stability in matter competition between cafe And restaurants, to meet the standards that have been set and are needed to survive in the competition that occurs. So in In this study, the author aims to analyze employee motivation and performance at Micro Coffee Enterprises using qualitative methods, namely interviews with employees and owners at Micro Coffee Enterprises. This study concludes that Micro Coffee Enterprises employees feel that overall, they are doing well. Which motivating they in Work However There is a little problem such as the lack of awareness of some employees regarding cleanliness in the workplace environment, and the lack of employees who implement work standards in accordance with the standards set by the Micro Coffee Business.